The effects of life style modification versus food supplementation on menopausal symptoms - Fouad, Suzanne (2023)
Forty seven females in the perimenopausal stage of life with mean age 46.04 ± 5.88 years participated on the food supplement consumption group, they consumed 75 g per day of a rusk (prepared from corn flour, wheat flour 72%, full cream milk powder, flaxseed oil, wheat germ, clove and cinnamon powder) for 2 months. They were compared with the control group (forty nine females with mean age 46.91 ± 5.39 years) who changed their foods habits to a healthy life style. Menopause rating scale and the biochemical analysis were comparable on day 1 and on day 60. The total menopause rating scale and its three subscales (psychological, urogenital and somatic), waist circumference, serum follicle stimulating hormone and estradiol in the corn rusk supplement group showed a statistically significant improvement. No significant difference was noted in the control group apart of the psychological subscale and waist circumference.